Targeted overexpression of parathyroid hormone-related peptide in chondrocytes causes chondrodysplasia and delayed endochondral bone formation. - Weir, E C (1996)
Parathyroid hormone-related peptide (PTHrP) was initially identified as a product of malignant tumors that mediates paraneoplastic hypercalcemia. It is now known that the parathyroid hormone (PTH) and PTHrP genes are evolutionarily related and that the products of these two genes share a common receptor, the PTH/PTHrP receptor. PTHrP and the PTH/PTHrP receptor are widely expressed in both adult and fetal tissues, and recent gene-targeting and disruption experiments have implicated PTHrP as a developmental regulatory molecule. Apparent PTHrP functions include the regulation of endochondral bone development, of hair follicle formation, and of branching morphogenesis in the breast. Herein, we report that overexpression of PTHrP in chondrocytes using the mouse type II collagen promoter induces a novel form of chondrodysplasia characterized by short-limbed dwarfism and a delay in endochondral ossification. This features a delay in chondrocyte differentiation and in bone collar formation and is sufficiently marked that the mice are born with a cartilaginous endochondral skeleton. In addition to the delay, chondrocytes in the transgenic mice initially become hypertrophic at the periphery of the developing long bones rather than in the middle, leading to a seeming reversal in the pattern of chondrocyte differentiation and ossification. By 7 weeks, the delays in chondrocyte differentiation and ossification have largely corrected, leaving foreshortened and misshapen but histologically near-normal bones. These findings confirm a role for PTHrP as an inhibitor of the program of chondrocyte differentiation. PTHrP may function in this regard to maintain the stepwise differentiation of chondrocytes that initiates endochondral ossification in the midsection of endochondral bones early in development and that also permits linear growth at the growth plate later in development.